Integrated Design System of Toroidal Field Coil for CFETR - 罗志仁 刘旭峰 杜双松 王忠伟 宋云涛 (Plasma science & technology, 2016)
Integrating engineering software is meaningful but challenging for a system code of a fusion device. This issue is seldom considered by system codes currently. Therefore, to discuss the issue, the Integrated Design System of TF Coil （IDS-TFC） has been worked out, which consists of physical calculation, CAD, and Finite Element Analysis （FEA）. Furthermore, an Integrated and Automatically Optimized Method （IAOM） has been created to address the integration and interfaces. The method utilizes a geometry parameter to connect each design submodule and achieve automatic optimization. Double-objectives optimization has been realized, confirming it is feasible to integrate and optimize engineering design and physical calculation. Moreover, IDS- TFC can also serve as a useful reference of integrated design processing for subsequent fusion design.